Uji stabilitas penyimpanan RC A amlodipine dengan metode kromatografi cair tingkat tinggi - Saing, Bungaran; Kustiyah, Elvi; Martina (Journal of Waste and Sustainable Consumption, 2024)
Background: One of the important components of health is the availability of drugs as part of public health services. This is because drugs are used to save lives, restore or maintain health. The pharmaceutical industry as a drug-producing industry has a strategic role in health service efforts to the community. Findings: Along with increasing education and public awareness of the importance of health, the pharmaceutical industry is required to provide drugs in adequate types and quantities and of good quality. Therefore, public access to drugs including availability and affordability for the entire community must be expanded. Access to drugs, especially essential drugs, is an obligation for the government and health service institutions, both public and private. Methods: Add with mobile phase to the limit mark, then homogenize (Solution S1 0.04 mg/ml). The solution to be tested for stability during the RC A Amlodipine area is stable. Storage is carried out in dark glass bottles and stored in a refrigerator at a temperature of 2-8 °C. Conclusion: This indicates that each new batch analysis can use the RC Amlodipine stock for a period of 4 months with a storage temperature of 2-8 °C. In this study, RC A Amlodipine which was weighed before the study each time the test was carried out was weighed once and made into a stock solution for 4 months. This study also carried out the potential for cost saving because every year 3 bottles are now 1 bottle, which is 96.5%.